AURAT WANITA DAN HUKUM MENUTUPNYA MENURUT HUKUM ISLAM - Muhammad Sudirman Sesse (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2016)
Aurat is minimum boundary part of human body which is mandatory is closed based on God comand. Aurat woman which is mandatory is closed is whole the body part, except face and two palms his arms and two its the feet palms. Such aurat constrain is applied by when woman is executing shalat and when dealing with men besides husband and the muhrim. As for when woman deals with the muhrim, or other men of which is not has lust and children which has not known the problem of aurat woman, limit aurat becomes clearance so that hair, neck, both hands until elbow and at twice until knee is not included in ketegori aurat which is mandatory is closed. Islam doesn't determine certain muslimah cloth model. along the length of fulfilling criterion to close aurat. At some stage, as according to the harsh and heavy work, Indonesia woman cannot close all the aurat is normally.